Differences in short-term food preferences following vertical sleeve gastrectomy and Roux-en-Y gastric bypass surgery. Issue 6 (November 2015) - Primeaux, Stefany D.; Tzeng, Tony H.; Allerton, Timothy D.; Chiang, Monica C.; Cosentino, Gina; Dubin, Robert L.; Varughese, Amy; Moore, Rachel; Geiselman, Paula J.; Greenway, Frank L.; Uwaifo, Gabriel I.
Summary: Bariatric surgery is effective in reducing body weight and obesity-related comorbidities. This study examined differences in the short-term effect of Roux en Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) on the hedonic rating of food. Predominantly black women with complicated obesity and a BMI > 50 g/m 2 completed a validated food preference questionnaire before and 1–3 months following surgery. Analysis of preference scores indicated that the preference for fat decreased with both surgeries. VSG also decreased the preference for sugar. Further studies are needed to evaluate long term effects of surgery on food preferences and to elucidate physiological mechanisms.